SOSIALISASI BAHAYA NARKOBA DAN HIV/AIDS DI MTS AL IKHWAN DESA BONGAS KECAMATAN CILILIN - Komarudin Komarudin (Jurnal Al Maesarah, 2023)
Currently, drug abuse in Indonesia is quite dangerous, especially among Madrasah students. Based on the findings of the 2018 BNN research in collaboration with LIPI, it was found that 3.21% of students or 2,297,492 students had abused drugs. The top two reasons students gave for using drugs, rated at 64% each, were curiosity and trial and error. Other factors included having fun (16.8%), being talked to by friends (6.6%), being framed (2.3%), and dealing with personal stressors (5.6%). The problem of drug use in adolescents is difficult to solve. Seminars on the dangers of drugs were held at MTS al Ikhwan Bongas as a method to reduce drug addiction among students.so that students are aware of the dangers associated with drug use and HIV/AIDS and ultimately choose not to get involved in them. The purpose of Community Service (PkM), which is one of the tridharma components of higher education, is to provide education to the public, especially students of MTS al Ikhwan, about the dangers of drugs and HIV/AIDS. The specific objective of this program is to help MTS Al Ikhwan students have a thorough understanding of the dangers associated with drugs, both in terms of normative theory and practice, as well as to develop a young generation that is safe and drug-free. This PkM activity includes seminars, counseling, and socialization regarding the dangers of drugs and efforts to prevent them from entering the Madrasah environment so that all Madrasah residents are aware of the spread of drugs. PowerPoint slides with easy-to-read content for students make up the majority of seminar media. The results of this program are expected to contribute to the realization of Madrasas that are free from drug trafficking and drug-free students.